THE DEVELOPMENT OF INTEGRATED SCIENCE WORKSHEET NESTED TYPE FOR 8th GRADE OF JUNIOR HIGH SCHOOL STUDENTS ON THE HUMAN DIGESTIVE SYSTEM MATERIAL - Safitri, Helmy; Zahra, Firda Az (Department of Science Education, 2024)
Science is one of the subjects whose learning is carried out in an integrated manner. Integrated science learning can be supported with integrated science worksheets. So far, the use of worksheets has not been maximized due to the availability of the worksheets themselves. In fact, with the integrated worksheet, the use of limited teaching materials can be more optimal. Therefore, it is necessary to develop a Nested-type integrated natural science worksheet. This study aims to produce a valid and practical Nested Type Integrated Science worksheet.The type of research used is Research and Development (R&D) using a 4-D research model consisting of four stages, namely, define, design, develop and disseminate. This worksheet was validated by three expert validators, namely science lecturers. The subjects of this study were class VIII students and science teachers. The object of research is the Nested Type Integrated Science worksheet.The results of this study obtained the following data: (1) The Nested type Integrated Science Worksheet that was developed was valid with a validity test result of 90.5% (very valid). (2) Nested Type Integrated Science LKS which was developed practically with practicality test results of 95.88% (very practical).